Comunicação pública e seu conteúdo online: uma análise das publicações da seção cidadania do portal da EBC - Silva, Vivian Duarte da (2018)
This dissertation investigates the characteristics of the content of the EBC Portal (Empresa Brasil de Comunicação) based on the foundations of public communication, its relationship with citizenship and the guidelines of webjournalism. For this analysis, the study was divided into two parts: one for the conceptual foundations of citizenship and public communication, and another for the deepening of the bibliographical and empirical study about EBC and its performance on the internet. The aim is to study theories and practices of citizenship, public communication and web communication established by EBC itself and the main researchers of these subjects, to identify the convergences between them and to relate them to the publications of the Citizenship section of the Portal. This analysis is important to reflect on the provision of public communication services in the digital network carried out by an institution linked to the Brazilian Executive Branch and that at the moment of the research positions itself as reference of public and citizen communication company. The relevance of the research is strengthened in the context of debates and questions about the EBC's performance from its inception to the later period of its legislative change. In this sense, the study also seeks to contribute with a look at the communication exercise on the internet aimed at the citizen in different moments of the EBC, besides expanding discussions, integrating reflections and critical thoughts about proposed contents as public and citizens. To do so, the research uses the methodology of Content Analysis to be applied in the publications of the EBC Portal in the Citizenship section of the years 2015, 2016 and 2017. From the inference of the analyzes of these periods, one can generally identify that in 2015, the content timidly passed through the guidelines of citizen public communication, that is, they existed, but did not fully prevail in the publications or were not widely studied. In 2016, some factors showed a slight evolution, but the year 2017 was marked by the greater distance of the practice from the internal and external foundations studied.